Peyer's Patches: The Immune Sensors of the Intestine - Camille Jung; Jean-Pierre Hugot; Frédérick Barreau (International Journal of Inflammation)
The gut-associated lymphoid tissue (GALT) consists of isolated or aggregated lymphoid follicles forming Peyer's patches (PPs). By their ability to transport luminal antigens and bacteria, PPs can be considered as the immune sensors of the intestine. PPs functions like induction of immune tolerance or defense against pathogens result from the complex interplay between immune cells located in the lymphoid follicles and the follicle-associated epithelium. This crosstalk seems to be regulated by pathogen recognition receptors, especially Nod2. Although TLR exerts a limited role in PP homeotasis, Nod2 regulates the number, size, and T-cell composition of PPs, in response to the gut flora. In turn, CD4+ T-cells present in the PP are able to modulate the paracellular and transcellular permeabilities. Two human disorders, Crohn's disease and graft-versus-host disease are thought to be driven by an abnormal response toward the commensal flora. They have been associated with NOD2 mutations and PP dysfunction.